On the regression analysis of menu price presentations toward customer buying decision in restaurant setting - Wijaya, Michael; Mayangsari, Lidia (Journal of Business and Management, 2020)
Abstract. Every restaurant must have competitive advantage to win and survive in the market and developing menu is one of the ways. Menu Price Presentation (MPP), one component in menu, can influence customer’s Willingness to Pay (WTP) mediated by Customer’s Price Perception (CPP). Odd or even price ending will create a different price perception. The use of numerical salience format and currency signs also carry semantic salience, a key factor in determining price perception. Then, the CPP will influence customer’s WTP as the customers have a tendency to use it in making a purchase decision. This study has a purpose to analyze the effect of numerical salience format, the inexistence of currency sign and the use of 0-price ending toward customer’s WTP. This study used quantitative approach through questionnaire with the characteristic of respondents: live in Bandung, have eating out frequency minimum two times a week and have a status of high school or college students. The data were analyzed using mediation regression analysis. The result is MPP significantly influence customer’s WTP fully mediated by CPP. The numerical salience format, the inexistence of currency sign and the 0-price ending will create a valuable perception and increase customer’s WTP.Keywords: Menu Price Presentation, Customer’s Price Perception, Customer Willingness to Pay, Restaurant’s Menu, Price Ending, Semantic Salience